2020
DOI: 10.18632/aging.102972
|View full text |Cite
|
Sign up to set email alerts
|

Role of mitochondrial quality control in the pathogenesis of nonalcoholic fatty liver disease

Abstract: Nutrient oversupply and mitochondrial dysfunction play central roles in nonalcoholic fatty liver disease (NAFLD). The mitochondria are the major sites of β-oxidation, a catabolic process by which fatty acids are broken down. The mitochondrial quality control (MQC) system includes mitochondrial fission, fusion, mitophagy and mitochondrial redox regulation, and is essential for the maintenance of the functionality and structural integrity of the mitochondria. Excessive and uncontrolled production of reactive oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 187 publications
(210 reference statements)
1
61
0
Order By: Relevance
“…Mitochondria are networked, plastic organelles that actively undergo fusion and fission to optimize their function and quality ( Li et al, 2020 ; Wang et al, 2020c ). Mitochondrial fusion allows the contents of partially damaged mitochondria to be intermixed and exchanged, presumably to counteract the decline of mitochondrial function ( Delmotte and Sieck, 2019 ; Hernandez-Resendiz et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondria are networked, plastic organelles that actively undergo fusion and fission to optimize their function and quality ( Li et al, 2020 ; Wang et al, 2020c ). Mitochondrial fusion allows the contents of partially damaged mitochondria to be intermixed and exchanged, presumably to counteract the decline of mitochondrial function ( Delmotte and Sieck, 2019 ; Hernandez-Resendiz et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary to explore whether TGP has the ability to normalize mitochondrial metabolism in cardiomyocytes. Recent studies have reported that disruption of mitochondrial dynamics, an alteration of mitochondrial morphology, functions upstream of mitochondrial metabolism switching [ 37 , 38 ]. However, it is unclear whether TGP affects cardiomyocyte function and viability by affecting mitochondrial dynamics and bioenergetics.…”
Section: Introductionmentioning
confidence: 99%
“…The ectopic development of fat storage in the liver was associated with alterations in the mitochondrial compartment. Both rats with steatotic liver and patients with steatohepatitis showed a reduced OXPHOS capacity, peripheral insulin resistance, and increased oxidative stress in hepatic mitochondria, although the ability to use fat as a metabolic fuel was increased [29,238,239]. The increase in fatty acid oxidation stimulates, in turn, ketogenesis as a compensatory mechanism.…”
Section: The 35-t2 and Lipid Metabolismmentioning
confidence: 99%